THE COST ASPECTS OF ENVIRONMENTAL PROTECTION MANAGEMENT (Research Bulletins of the Faculty of Economic Sciences, 2021)
he aim of the article is presenting the issues connected with the cost aspects of environmental protection management. The specificity of environmental protection environment, classification of environmental protection expenses and the outline of the environmental protection cost account have been presented. The issues raised in the article are significant for the reason that there are no solutions connected with mea-surement, records, registration, environmental protection expenses settlement which makes its managing difficult. The content of the article has been based on the literature within management, environmental protection, accounting and cost account.
Keywords: the environmental protection, cost, outlays, expense, management, enter-prise, cost account